Tinjauan Literatur Sistematis tentang Arsitektur Nusantara: Definisi, Posisi, dan Persepsi Audiens Ilmiah - Muhammar Khamdevi; Daniel Bun Joel (Ruang-Space: Jurnal Lingkungan Binaan)
The study of Nusantara Architecture has been a subject of debate since it was first introduced. To this day, the concept continues to spark controversy, particularly among many academic audiences who view it as a representation of old local architecture rather than a body of design knowledge. This research aims to examine the definition and position of Nusantara Architecture further and explore the perceptions of academic audiences regarding the concept based on existing literature. By conducting a systematic literature review, this study builds upon previous research that analyzed trends in Nusantara Architecture studies and provides deeper insight into how this architecture is perceived and defined in academic discourse. The findings indicate that the definition of Nusantara Architecture lies in the formal aspects of traditional architecture, specifically in its design knowledge. In relation to Western architecture, it distinguishes itself from both traditional and vernacular architecture. However, it cannot fully detach from the knowledge of these two forms, which contribute to its development. The majority of academic audiences perceive its definition and position differently, focusing more on its material aspects. Keywords: nusantara architecture; traditional architecture; vernacular architecture; systematic literature review